Participatory Watershed Development: A Case Study of Antisar Watershed in Gujarat State - G. L. Bagdi; R. S. Kurothe (Indian Journal of Extension Education, 2013)
The study was conducted during 1997-2003 in the Integrated Wasteland Development Project (IWDP), Antisar watershed, located in Kapadwanj Taluka of Kheda district in Gujarat state in India. The Antisar watershed was developed in participatory mode by involving local people in decision making and adoption of various soil and water conservation (SWC) interventions for sustainable development. In the participatory watershed development process, a set of suitable technologies were tested by farmers on their farm as well as community land in the watershed area with their part contribution as money or labour and under guidance of multidisciplinary team of scientists of Project Implementing Agency (PIA). Bottom-up approach was adopted in the Antisar watershed development by involving the local farmers to take decisions in planning, implementation and maintenance of SWC practices adopted for the watershed development. The participation of male and female beneficiary farmers was high in the watershed development programme. The Antisar watershed development programme was fruitful up to the satisfaction of farmers as well as scientists of PIAto mitigate the water scarcity condition in the area due to ground water recharge for sustainable agricultural production.